A rare cause of retroperitoneal mass: Castleman's disease - Satyaprakash Jindal; G K Adithya; Varun Madaan; Rigved Gupta; Sandeep Vohra; Vivek Tandon; Deepak Govil (Apollo Medicine)
Castleman's disease is a rare lymphoproliferative disorder. It is a pathological diagnosis and rarely diagnosed before surgery. Presentation of disease may be unicentric or multicentric. We are reporting a case of unicentric Castleman's disease presenting as an asymptomatic retroperitoneal mass. The ultrasound-guided aspiration of the lesion was inconclusive. Complete en bloc resection was done and was reported as Castleman's disease after pathological analysis. Pathogenesis of Castleman's disease is not well defined, but interleukin-6 and vascular endothelial growth factor are thought to have a significant role. Two pathological variants have been described as follows: hyaline vascular and plasma cell type. The treatment of unicentric disease is complete resection. Multicentric disease may be associated with human immunodeficiency virus and human herpes virus-8 infection and requires systemic treatment in the form of steroids, chemotherapy, radiotherapy, or immunotherapy.